The quality of life in patients with ulcerative colitis with regard to demographic and clinical factors - Stanisławska, Joanna; Zubrzycka, Renata; Talarska, Dorota (Nursing Problems / Problemy Pielęgniarstwa, 2015)
Background. Ulcerative colitis (colitis ulcerosa), as the whole group of non-specific bowel inflammations, is a disease whose aetiology has not been fully understood. It is characterised by bowel as well as general symptoms which affect patients’ everyday life. Aim. The quality of life of patients with ulcerative colitis with regard to demographic and clinical factors. Material and methods. Research has been conducted in the period from 2010 to 2012 among 258 patients with ulcerative colitis staying in the Gastroenterology and Human Nutrition Ward in Clinical Hospital no 2 in Poznan and the users of: www. Drosscrohn.home.pl forum. The method of diagnostic survey, inquiry technique. RFIPC questionnaire and a survey helping to collect demographic and clinical data. Results. A study assessed quality of life of the respondents. The mean for the whole group was 48.09 points. The most numerous group of patients who scored above 38.7 points in the questionnaire (meaning worse quality of life) were women (56.2%). Good quality of life (RFIPC below 38.7 points) was more frequently found in men but only in two domains: intimate life 34.9 points and body stigmatisation 36.8 points. Conclusions: Subjective assessment of quality of life in women is influenced by: the disease, intimate life, complications and body stigmatisation. The low quality of life is more frequently present in: women, patents with aggravated course of the disease, inhabitants of villages, patients with vocational or primary education, patients professionally inactive as well as patients whose disease lasted 2 years and above 10 years.